Dietary habits of Byzantine Kovuklukaya (Sinop, Türkiye): an isolated society or ostracized people? - Özdemir, Kameray; Itahashi, Yu; Yoneda, Minoru; Erdal, Yılmaz Selim (Frontiers in Environmental Archaeology, 2025)
IntroductionDuring the medieval period, cultural attitudes toward leprosy often involved the exclusion of infected people from general society. People suffering from leprosy were often moved to live in separate places such as a specific district, village, or hospital. Such actions are social implications of how the disease and its sufferers were viewed and dealt with. This study aims to investigate whether Kovuklukaya was inhabited by segregated lepers.MethodsThis was conducted by examining diet of individuals using stable isotope analysis of bulk bone collagen and compound-specific amino acids, and integrating these results with osteoarchaeological, pathological, and ethnographic data.ResultsThe stable isotope values reveal a terrestrial C3 diet with little inclusion of C4 plants. The probable source of the animal protein would appear to be sheep and/or goat. Although there is a broad range of available and potentially exploited and consumed food resources in the Black Sea region, the narrow range of the isotopic values would suggest a similarity in the availability or choice of food resources at the different sites in the region.DiscussionA wide diversity in consumed food resources of ostracized people from different dwellings may be expected. However, the isotopic values suggest that the people of Kovuklukaya consumed a narrow range of food resources. This similarity may arise from the mountainous environment which may restrict the range of available food resources, but is more probably due to common dietary habits such as the regular consumption of the same kinds of foods, eating from the same pots, etc., in a closely related group, kin, or family. The homogeneous characteristic of the dietary habits at Kovuklukaya supports the premise that Kovuklukaya was a small mountain village or hamlet rather than a leper colony.